Seronegative generalised myasthenia gravis: clinical features, antibodies, and their targets. - Vincent, A; Bowen, J; Newsom-Davis, J; McConville, J (2003)
Myasthenia gravis (MG) is a well-recognised disorder of neuromuscular transmission that can be diagnosed by the presence of antibodies to the acetylcholine receptor (AChR). However, some patients (about 15%) with generalised MG do not have detectable AChR antibodies. There is some evidence, however, that this "seronegative" MG is an antibody-mediated disorder. Plasma from patients with the disorder seems to contain various distinct humoral factors: IgG antibodies that reversibly inhibit AChR function; a non-IgG (possibly IgM) factor that indirectly inhibits AChR function; and an IgG antibody against the muscle-specific kinase (MuSK). The presence of antibodies against MuSK appears to define a subgroup of patients with seronegative MG who have predominantly localised, in many cases bulbar, muscle weaknesses (face, tongue, pharynx, etc) and reduced response to conventional immunosuppressive treatments. Moreover, muscle wasting may be present, which prevents complete response to these therapies.